Coverage of religious news in the Kazakh media: wearing the hijab in schools - Kap Е.; Shagatayeva Ә (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2026)
This research is devoted to the analysis of a highly relevant and timely topic: how the issue of wearing the hijab in state schools of Kazakhstan is reflected in the media. In recent years, the topic of the wearing of hijab at school has repeatedly emerged in society and become the subject of intense social discussions, making this research particularly significant. This study aims to fill a significant gap in the current research landscape. Despite the media’s frequent coverage of hijab-related news, opinions, and analyses, the representation of this topic in the media remains largely unexplored. The research will focus on analyzing the portrayal of a religious symbol in the media through content analysis, particularly how media outlets with different funding sources, such as Azattyq and Tengrinews, covered the issue of hijab-wearing in schools from 2017 to 2024. The scientific and practical significance of the study lies in the fact that the analysis of the representation of the headscarf in the media makes it possible to identify how not only religious aspects but also broader ideological, cultural, and legal contradictions in society are reflected. The research employed a comprehensive approach, utilizing both quantitative and qualitative content analyses, as well as the method of critical discourse analysis. These methods were used to systematically select and compare 20 articles published in the media outlets Azattyq and Tengrinews between 2017 and 2024.